Multisensory processing impacts memory for objects and their sources. - Duarte, Shea E.; Yonelinas, Andrew P.; Ghetti, Simona; Geng, Joy J. (Memory & Cognition, 2025)
Multisensory object processing improves recognition memory for individual objects, but its impact on memory for neighboring visual objects and scene context remains largely unknown. It is therefore unclear how multisensory processing impacts episodic memory for information outside of the object itself. We conducted three experiments to test the prediction that the presence of audiovisual objects at encoding would improve memory for nearby visual objects, and improve memory for the environmental context in which they occurred. In Experiments 1a and 1b, participants viewed audiovisual–visual object pairs or visual–visual object pairs with a control sound during encoding and were subsequently tested on their memory for each object individually. In Experiment 2, objects were paired with semantically congruent or meaningless control sounds and appeared within four different scene environments. Memory for the environment was tested. Results from Experiments 1a and 1b showed that encoding a congruent audiovisual object did not significantly benefit memory for neighboring visual objects, but Experiment 2 showed that encoding a congruent audiovisual object did improve memory for the environments in which those objects were encoded. These findings suggest that multisensory processing can influence memory beyond the objects themselves and that it has a unique role in episodic memory formation. This is particularly important for understanding how memories and associations are formed in real-world situations, in which objects and their surroundings are often multimodal.